Determinants of the Utilization of the Medan Berkah Health Insurance Program (JKMB) - Firzah, Nyak; Gurning, Fitriani Pramita; Susilawati, Susilawati (GLOBAL HEALTH SCIENCE GROUP, 2024)
Universal Health Care (UHC) means that everyone has access to high-quality healthcare at the time and location they need without financial hardship. UHC is achieved with the JKN program which in Medan City applies the free Medan Berkah Health Insurance (JKMB) program for Medan residents with Medan KTP/KK. The achievement of health insurance participation in the Pasar Merah Medan Puskesmas working area until February 2024 is still 71% of the total population of the Puskesmas working area. The study aims to analyze the determinants of the utilization of Medan Berkah Health Insurance (JKMB) in the Working Area of the Pasar Merah Medan Health Center. The study used quantitative with a cross-sectional design. The population was 27,378 people and a sample of 100 respondents used lameshow. The sampling technique uses simple random sampling. Data is collected using questionnaire. Analyze data using univariate and bivariate test using SPSS Statistics. The results showed that there was a correlation between complaints of illness (p-value 0.001), education (p-value 0.002), knowledge (p-value 0.048) with the utility of JKMB, and there was no correlation between employment (p-value 0.685), dan mileage (p-value 0.637) with the utility of JKMB.